PENGARUH RESILIENCE DAN LEARNING AGILITY TERHADAP KINERJA KARYAWAN PADA PT. DOK DAN PERKAPALAN KODJA BAHARI GALANGAN CIREBON - Laura Rafidah; Sari Laelatul Qadriah; Risdianto (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the influence of Resilience and Learning Agility on employee performance at PT. Dok dan Perkapalan Kodja Bahari (Persero) Cirebon Shipyard. This research is based on the trend of declining employee performance. The problem is suspected to be caused by high work pressure that is not balanced with employees' mental endurance and personal ability to adapt quickly. The research method used is a quantitative approach. The population for this study consists of all 70 employees, and the sampling technique used is saturation sampling. Data analysis techniques include Instrument Testing (Validity and Reliability Tests), Normality Test, Multiple Linear Regression Test, and Hypothesis Testing (Partial Test / t-Test, and Simultaneous Test / F-Test) with the help of SPSS Version 22 software. The study shows that the Resilience variable has a positive and significant influence on employee performance, meaning the higher the level of resilience an employee has, the more optimal their performance. Furthermore, Learning Agility has a positive and significant influence on employee performance, which indicates that employees who have the ability to adapt and learn quickly tend to have better performance. Subsequently, Resilience and Learning Agility together (simultaneously) have a significant influence on employee performance. Both variables play a strong role in improving employee performance, which can ultimately boost productivity and optimal achievement for the company.